The changing role of axillary treatment in breast cancer: Who will remain at risk for developing arm morbidity in the future?. Issue 5 (October 2015) - Lopez Penha, T.R.; van Roozendaal, L.M.; Smidt, M.L.; Boersma, L.J.; von Meyenfeldt, M.F.; Voogd, A.C.; Heuts, E.M.
Abstract Primary aim is to give an overview of changes in axillary staging and treatment of breast cancer patients. Secondly, we aim to identify patients with a high arm/shoulder morbidity risk, and describe a strategy to improve early detection and treatment. Recent and initiated studies on axillary staging and treatment were evaluated and clustered for clinically node negative and clinically node positive breast cancer patients, together with studies on pathology, detection and (surgical) prevention and treatment of lymphedema. For clinically node negative patients, the indication for axillary lymph node dissection in sentinel node positive patients is fading. On the contrary, clinically node positive patients are routinely subjected to an axillary lymph node dissection, in combination with other therapies associated with an increased lymphedema risk, such as mastectomy, adjuvant radiation- and (taxane-based) chemotherapy. Techniques for prevention, early detection and (surgical) treatment of lymphedema are being developed. Axillary staging and treatment in breast cancer patients with a clinically node negative status will become less invasive, thereby reducing the incidence of morbidity. Nevertheless, in patients with a clinically node positive status, aggressive treatment will still be required for oncologic control. For these patients, a surveillance program should be implemented in order to apply (curative) surgical treatment for lymphedema.